Family appointments & investors' reaction - Shi, Adelyne Mei Shan (Nanyang Technological University, 2009)
The purpose of this study is to investigate, in the Singapore context, investors’ reaction to family ties in public firms. More specifically, the study will look at investors’ reaction following the announcement of family relations within a firm, and whether the quality of corporate governance will influence these investors’ valuation. Family announcements were retrieved from the Singapore Exchange (SGX) website for a total of 401 firms. Excluding confounding announcements, a total of 101 family announcements were included in the financial-event study analysis. We found that investors, on average, reacted negatively but not significantly to family relation announcements. However, the regression analysis suggests that investors will react more positively to family announcements when firms implement good governance practices. These results suggest that while investors may be equivocal to the presence of family ties in firms, they appear more positive when these firms adopt good governance practices that may mitigate the potential negative consequence of family ties within firms.